Influence of Film-Cooling Hole Arrangement on Mechanical Properties of Cooled Turbine Blade Based on the Crystal Plastic Theory. (8th August 2019) - Lian, Y.; Xu, Z.; Pei, H.; Liang, C.; Zhang, Y.; Wen, Z.; Yue, Z.
Abstract : The crystal plastic theory was used to examine the effect of film-cooling hole arrangements on mechanical properties of cooled turbine blade. The finite element method was used to analyze the maximum von Mises stress and resolved shear stress of an octahedral slip system considering the number of rows, diameter, spacing, and tangential-to-longitudinal hole spacing ( h/l ) ratio. The different arrangements were found to have a significant influence on the maximum von Mises stress and resolved shear stress. For the triangular arrangement, the von Mises stress and resolved shear stress were highest with double rows, followed by a single row and then triple rows. For the quadrilateral arrangement, the stresses were highest with double rows, followed by triple rows and then a single row. Increasing the spacing or decreasing the diameter reduced the maximum von Mises stress and weakened the multi-hole interference effect. Both the maximum von Mises stress and resolved shear stress decreased with the h/l ratio.